Emerging approaches for antagonizing the aryl hydrocarbon receptor - Dvořák, Zdeněk; Mani, Sridhar; Vondráček, Jan (Trends in pharmacological sciences, 2025)
Antagonizing the aryl hydrocarbon receptor (AhR) is a highly pertinent pharmacotherapeutic strategy. To overcome the drawbacks of existing AhR antagonists, novel molecules that can selectively target canonical and noncanonical AhR pathways are urgently needed. Recent reports on the structures and functions of cytosolic and nuclear AhR-protein complexes have allowed for understanding structural determinants for intrinsic activity and functional selectivity of AhR ligands. This new information regarding AhR surface interactions has opened new avenues for the development of novel AhR antagonists. Achievable strategies include the negative allosteric modulation of AhR and the disruption of AhR-protein and AhR-DNA interfaces using peptidomimetics or small molecules. Here, we discuss such novel approaches that may lead to new AhR-targeted therapeutics.
Keywords: AhR receptor; Animals; Ligands; lidé; functional selectivity; zvířata; Receptors, Aryl Hydrocarbon; receptory aromatických uhlovodíků; antagonism; allosteric modulation; ligandy; Humans